Pengembangan Media Pembelajaran Komik Digital tentang Bipolar untuk Remaja - Bunga Anindita Pramono; Handaru Jati (Department of Electronics and Informatics Engineering Education, 2024)
This research is a digital comic-based learning media development research that discusses bipolar mental disorder. This study aims to produce digital comic-based learning media about bipolar disorder and also to provide adolescents with an understanding of bipolar and how adolescents can deal with bipolar sufferers. This study uses a type of research and development research design. The research procedure used is Borg and Gall's modified procedure which includes the following: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, ( 6) product trials, (7) product revisions. The results of the validation of learning media are: (1) media experts assess learning media as feasible with a value of 3,35. (2) based on the results of interviews, adolescents already understand and feel digital comics can help them to understand topics about mental health more easily.